Desarrollo de un brandbook para la empresa de tatuajes y piercings Kontratattoo - Sanchez Vilchez, Jacqueline (2021)
This work focuses on the development of a brandbook for the tattoo and piercing company: Kontratattoo. Its development began with a previous investigative work, aimed at the brand's target audience; the purpose was to know their interests, their language and preferences in order to achieve identification with what the brand communicates for them, seeking to attract them as potential new customers. Therefore, a virtual survey aimed at them and a focus group with people selected from the questionnaire were carried out to get the needed information. This research helped to set the owner's vision; an artist, musician of punk, rock and black metal genres, who was looking to create a brand with which he feels more identified. Continuing with that purpose, and after conceptualizing the idea, the graphic line was decided so as the proposed strategies that will be shown in the brandbook, which contains the language of these subcultures marked, seeking to merge the artistic category of tattoo with the aforementioned countercultural scene. In order to achieve this photographic and audiovisual records were made, graphic materials were elaborated and strategies for the contents were applied. Starting with the design of an imagotype, conceptualizing the graphic line oriented to the target audience and creating graphic pieces for networks, likewise, a mockup for a website was also designed and finally tentative merchandising proposals.